Performance of user relay cooperative NOMA system with partial and imperfect CSI - Kim, Nam-Soo (International Journal of Engineering and Technology, 2018)
In this paper, we consider a cooperative non-orthogonal multiple access (NOMA) system with user relay under partial and imperfect channel state information (CSI). For a user cooperation, a relay is selected among near users using partial CSI to reduce the delay for the selection process. During the relay selection process, the channel errors caused by the imperfect CSI is considered. And selection combining is applied to the far user for spatial diversity. Outage probabilities of the relay and far user are derived separately in closed-form as a function of the channel errors. It is noticed that the max relay selection strategy is recommendable under fewer channel errors. However, as the channel errors increases, the performance of the relay with max selection degrades and finally approaches that of the randomly selected relay. It means the max relay selection strategy is not effective for the performance gain under high channel errors. Though the performance of the far user degrades as the channel errors increases, the degradation is less sensitive due to the selection combining. We noticed that the end-to-end outage probability with max relay selection is slightly increased with channel errors. However, the performance degradation is more sensitive with random relay selection. To demonstrate the accuracy of the developed analytical results, we showed Monte Carlo simulation results are perfectly matched with the analytical results.Â Â